Evaluation of home based insulin therapy among pediatric patients with type I diabetes mellitus - A prospective analytical study - Soundararajan N; Thangavel A; Vidjeadevan D; Annamalai Vijayaraghavan (Journal of Medical and Scientific Research)
Background: Home based insulin therapy is one of the major challenges faced by the Type I diabetes mellitus (T1DM) patients with regards to the injection technique and correct dosing. The study aimed to assess the home based insulin therapy and its complications and to evaluate the impact of counselling on home based insulin therapy among Type I diabetes mellitus patients.